Comparative Study on Efficiency Analysis of Fixed and Dual-Axis Solar Tracking System - Oli, Ajay; Sharma, Saugat; Adhikari, Pratham; Neupane, Deepak; Khanal, Santosh; Labh, Shacheendra Kishor (Journal of Engineering and Sciences, 2024)
Solar energy is a crucial renewable energy source, offering sustainable solutions to address energy demands and combat climate change. Maximizing the efficiency of solar energy harvesting is essential for widespread adoption and integration into the energy landscape. Solar tracking systems play an important role in increasing the efficiency of solar panels by optimizing their orientation towards the sun throughout the day. This research presents a comparative analysis of the efficiency of dual-axis solar tracking systems using Light-Dependent Resistors (LDRs) as input devices. A closed-loop tracking technique is implemented to adjust the position of the solar panels based on real-time sensor feedback. A comparative study between LDRs demonstrates their effectiveness in detecting the sun's position, despite limitations such as susceptibility to ambient light conditions and saturation to light intensity. Through experimental evaluation and data analysis, this study provides valuable insights into the power output and assessment of efficiency variation of dual-axis solar tracking systems offering applications for optimizing solar energy harvesting in practical scenarios.